2009
DOI: 10.1097/yco.0b013e32832eb5c3
|View full text |Cite
|
Sign up to set email alerts
|

Special education for intellectual disability: current trends and perspectives

Abstract: Direct, systematic instruction in reading, arithmetic, and daily living skills is the most effective approach to teaching students with intellectual disabilities. Basic concepts and logic suggest that special and general education cannot be equivalent. We conclude that what students are taught should be put ahead of where they are taught. Our fundamental concern is that students with intellectual disabilities be respected and be taught all they can learn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Although many special education programs, particularly at the secondary level, have separate programs in place that teach daily living skills, other programs are trending toward inclusion of students with intellectual disability in regular education classrooms (Kauffman & Hung, 2009). Although the majority of parents in our study reported that school goals were appropriate for their children, this may not be generalizable to all students with FXS or another form of intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Although many special education programs, particularly at the secondary level, have separate programs in place that teach daily living skills, other programs are trending toward inclusion of students with intellectual disability in regular education classrooms (Kauffman & Hung, 2009). Although the majority of parents in our study reported that school goals were appropriate for their children, this may not be generalizable to all students with FXS or another form of intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Some changes occurred in the structure of classes and evaluations. Kauffman and Hung (2009) indicated that direct, systematic instruction is effective for students with intellectual disabilities; video calls allowed us to impart such instruction and evaluate the teaching content as well as the knowledge learned. As Pather et al (2020) reported, given the concentrated efforts by all in the face of global changes, the uncertainties and potential vulnerability seem to guarantee an effective learning environment, whenever possible, and even serve as a stimulus for adapted and improved teaching.…”
Section: Challenges In Teaching Human Anatomy To Students With Intellmentioning
confidence: 99%
“…Disabilities are mistaken as merely another kind of diversity to be accepted (Kauffman & Landrum, 2009 for commentary). Moreover, concern for inclusion has seemed to overshadow concern for effective teaching, an unfortunate turn of events and proposed policy (Kauffman & Badar, 2014;Kauffman & Hung, 2009;Kauffman, Anastasiou, Badar, Travers, & Wiley, 2016).…”
Section: Inclusionmentioning
confidence: 99%